A turn-on near-infrared fluorescent probe with rapid response and large Stokes shift for the selective and sensitive detection of zinc(ii) and its application in living cells. Issue 18 (17th April 2019) - Zhang, Weixia; Jin, Xinxin; Chen, Wei; Jiang, Chunhui; Lu, Hongfei
Abstract : Herein, a new near-infrared turn-on fluorescent probe, YPT, was designed and synthesized for the rapid detection of Zn 2+, which exhibited low limit of detection for Zn 2+ (12 nM) as well as a favorable large Stokes shift ( λ em − λ ex = 168 nm). Abstract : Herein, a new near-infrared turn-on fluorescent probe, YPT, was designed and synthesized for the rapid detection of Zn 2+, which exhibited low limit of detection for Zn 2+ (12 nM) as well as a favorable large Stokes shift ( λ em − λ ex = 168 nm). In addition, the probe showed rapid detection progress within 30 s, accompanied by a distinct change in fluorescence from colorless to bright red. Moreover, the sensing mechanism ofYPT towards Zn 2+ was supported by the Job's plot, HR-MS analysis, 1 H NMR titration analysis and density functional theory (DFT) results. In addition, YPT was applied as a visible test strip for the detection of Zn 2+ . Finally, the NIR fluorescence imaging of Zn 2+ was successfully performed in living cells using this probe. All the results indicate that this probe can be used to detect Zn 2+ in both solution and living systems.